Epigenome and three-dimensional genome architecture remodeling during NDM29-mediated retro-transformation of neuroblastoma cells - Francesca Baldini; Aldo Pagano; Lama Zeaiter; Paolo Bianchini; Hawraa Zbeeb; Alberto Diaspro; Laura Vergani (PLoS ONE, 2025)
Neoplastic transformation of mammalian cells involves intricate interactions between genetic, epigenetic and architecture modifications of the nucleus. Neuroblastoma is a malignant pediatric tumor with high biological and clinical heterogeneity representing a challenging model of study. We aimed to explore the changes in genome architecture and epigenetics being associated with neuroblastoma malignancy. We employed the neuroblastoma cell line SKNBE2 overexpressing the ncRNA NDM29 to differentiate from highly malignant into neuron-like cells. By 3D confocal microscopy, we explored the nuclear architecture (volume, elongation, compactness, and chromatin density). Using super-resolution microscopy (STED) and histone H3 immunolabelling we assessed the epigenetic rearrangement, and by enzyme-linked immunoassay the global DNA methylation. Then we assessed the mRNA expression of the main epigenetic modifying enzymes by quantitative PCR, and the expression of NF-κB-regulated genes by cDNA microarray. Compared to malignant NB cells, the NDM29-overexpressing cells, assuming a neuron-like phenotype, exhibited smaller and more elongated nuclei, redistribution of H3K9-acetylated and -methylated chromatin domains and DNA hypermethylation. In line with these results, in neuron-like cells the acetyltransferase KAT2A and the DNA methyltransferase DNMT1 were up-regulated, while most of NF-κB-regulated genes were down-regulated. Our findings reveal modifications of the nuclear structure and epigenome during neuroblastoma retro-transformation induced by NDM29 overexpression, with impacts on gene expression. These results offer potential insights into better understanding the mechanism of neuroblastoma malignancy in terms of chromatin rearrangements, opening exciting prospects for prognostic and therapeutic approaches with a focus on the nuclear level.